2019
DOI: 10.1002/jso.25391
|View full text |Cite
|
Sign up to set email alerts
|

Similar local recurrence but better function with curettage versus resection for bone giant cell tumor and pathological fracture at presentation

Abstract: Background There are conflicting reports for the outcome of the patients with giant cell tumor of bone (GCTB) and pathological fracture at presentation treated with curettage or resection. This study compared local recurrence, complications, and function after curettage versus resection for these patients. Materials and Methods We retrospectively studied the files of 46 patients with histologically confirmed GCTB of the extremities admitted and treated from 1982 to 2015. The median follow‐up was 79.5 months (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 45 publications
(93 reference statements)
2
26
0
1
Order By: Relevance
“…Only five patients were found to have secondary early osteoarthritis during follow-up, and surgical treatment was not required. Therefore, we have also proven that subchondral bone grafting can avoid the direct damage of cement to cartilage and reduce the incidence of postoperative complications without affecting the recurrence rate, which was consistent with that reported in previous studies (7, 29, 30).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Only five patients were found to have secondary early osteoarthritis during follow-up, and surgical treatment was not required. Therefore, we have also proven that subchondral bone grafting can avoid the direct damage of cement to cartilage and reduce the incidence of postoperative complications without affecting the recurrence rate, which was consistent with that reported in previous studies (7, 29, 30).…”
Section: Discussionsupporting
confidence: 92%
“…SR, as an excellent surgical method for oncological prognosis, was recommended for GCTB of the proximal fibula (31), distal radius (32), and part of Campanacci grade III (Figure 5) (5, 29, 30). Medellin et al (5) reported a lower recurrence rate in patients with Campanacci grade III using SR than using EC through a comparative study, and the results were further confirmed by Renard et al (33).…”
Section: Discussionmentioning
confidence: 99%
“…Tsukamato et al . reported that the rate of local recurrence for these patients was 22.0% after curettage and 8.8% after resection, demonstrating the superior effects of en bloc resection in reducing the recurrence rate of GCTB 39 . Tumor prosthesis replacement is the common method for reconstruction after en bloc resection.…”
Section: Discussionmentioning
confidence: 96%
“…The difference between curettage and wide resection is always one of the hotspots in the treatment of GCT of bone with pathological fracture [16,18]. Recent studies have shown that curettage can achieve local tumor control rates similar to resection while reducing the incidence of complications [2]. At the same time, other recent studies have also shown that pathological fractures are not a risk factor for recurrence, and the presence of a pathological fracture should not preclude the decision to perform curettage [18].…”
Section: Discussionmentioning
confidence: 99%
“…Giant cell tumor (GCT) of bone accounts for approximately 5% of all primary bone tumors [1]. The rate of pathological fracture at presentation in these patients is 4% to 50% [2], with 12% of the fracture located at the distal end of the femur [2]. Pathological fracture of distal femur giant cell tumor (GCT) frequently leads to joint surface defect, which is challenging to be repaired.…”
Section: Introductionmentioning
confidence: 99%